Research on Wi-Fi location algorithm based on TDOA and RSSI - Zhang, Yudi (Nanyang Technological University, 2020)
In recent years, with the rapid development of mobile communication technology, wireless positioning technology has become an indispensable function in mobile communication system. In these years, the research results show that in the indoor environment, due to the complexity of the environment and positioning needs, the Wi-Fi positioning system which has high network coverage and high positioning accuracy is widely concerned. At the same time, due to the better stability and signal strength of dual-band Wi-Fi, dual-band Wi-Fi is used to improve the accuracy of positioning. This report focuses on the location algorithm based on TDOA and RSSI. It mainly introduces triangle positioning algorithm, three location algorithms based on TDOA, and location fingerprinting algorithm based on RSSI. According to the principle of various algorithms, MATLAB is used to simulate and analyze the algorithms, and the performance of various algorithms under different conditions is compared. In the location algorithm of TDOA, the calculation method of dual bands Wi-Fi is proposed.